(3CMGSf GdeMGSfs - (3EHQGgje Hf CMeO Hf eMeO GdMfHdj, GHf eYGdj GdQbj, HQgGf GdOjf CHh ESMGb , J (B703 (3g`s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CJe Ydi YHGOg GdUGdMjf GdfYeI gPG cJGH ENJQJ ajg eG CMSf eGai cJGH UahI GdUahI dEHf GdLhRi JZeOg Gddg HQMeJg s
(3BNQgG (B:s
(3eNdhb fXQ GdjfG aGSJZfjfG acja dh fXQfG EdjfG GdNGdb s
(3GfXQ GdbSe GdChd HQbe (B10s
(3hGdbSe GdKGdK HQbe (B871s
(3fSNI NGeSI hgh oeNJUQ UaI GdUahI dGHf GdLhRjs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs